Obese adolescents who gained/maintained or lost weight had similar body composition and cardiometabolic risk factors following a multidisciplinary intervention - Josiane Aparecida Alves Bianchini; Danilo Fernandes da Silva; Luzia Jaeger Hintze; Vanessa Drieli Seron Antonini; Carlos Andres Lopera; Jessica McNeil; Nelson Nardo Junior (Elsevier, 2014)
This study aimed to assess the impact of a multidisciplinary program of obesity treatment (MPOT) on adolescents who have maintained/gained weight or lost weight. Eighty-six adolescents aged 10-18 years were allocated in either the intervention group (IG; n = 44) or the control group (CG; n = 42). Each group was divided into two more groups: weight maintenance/gain and weight loss, as assessed after the intervention. The MPOT lasted 16 weeks and was conducted by a multidisciplinary team based on cognitive-behavioral therapy. We analyzed body composition and cardiometabolic parameters prior to and after the intervention. Adolescents from the IG who lost weight showed improvements in maximal oxygen uptake (23.54 ± 5.30 mL/kg/minute vs. 25.39 ± 5.63 mL/kg/minute), body fat percentage (49.29 ± 6.98% vs. 46.75 ± 8.56%), triglyceride levels (116.58 ± 46.50 mg/dL vs. 101.19 ± 43.08 mg/dL), diastolic blood pressure (75.81 ± 8.08 mmHg vs. 71.19 ± 6.34 mmHg), and the number of risk factors for metabolic syndrome (2.00 ± 1.06 vs. 1.58 ± 1.10). Adolescents from the IG who gained/maintained weight reported reduced body fat percentage (48.81 ± 5.04% vs. 46.60 ± 5.53%), systolic blood pressure (123.39 ± 14.58 mmHg vs. 115.83 ± 7.02 mmHg), diastolic blood pressure (74.83 ± 9.91 mmHg vs. 68.78 ± 5.95 mmHg), and number of risk factors for metabolic syndrome (from 1.67 ± 1.09 to 1.11 ± 0.68), and their lean mass (39.00 ± 7.20 kg vs. 41.85 ± 7.53 kg) and maximal oxygen uptake (23.74 ± 4.40 mL/kg/minute vs. 25.29 ± 5.17 mL/kg/minute) increased in a manner similar to those of adolescents who lost weight. Furthermore, we noted significant decreases in body mass index, body fat (kg), glycemia, and waist circumference in CG adolescents who lost weight, whereas those in the CG who maintained/gained weight had an increase in body mass index, hip circumference, body fat (kg), and lean mass. A 16-week MPOT promoted positive changes in body composition and cardiometabolic risk factors independently of weight changes.